Influence of surface sealing on color stability and roughness of composite submitted to ultraviolet-accelerated aging - Catelan, Anderson; Umeda Suzuki, Thais Yumi [UNESP]; Becker, Francisco; Fraga Briso, Andre Luiz [UNESP]; Santos, Paulo Henrique dos [UNESP] (Wiley-Blackwell, 2017)
Aim: In the present study, we evaluated the influence of surface sealing on color stability and surface roughness of a composite resin after accelerated artificial aging. Methods: Thirty-two specimens of a composite were prepared. After 24 h, the specimens were polished and divided into four groups (n = 8), according to the surface sealant used, including the control, which had no sealant application. Baseline color was measured according to the CIELab system using a reflection spectrophotometer. Surface roughness was determined using a pro-filometer with a cut-off of 0.25 mm. After these tests, specimens were aged for 252 h in an ultraviolet (UV)-accelerated aging chamber. Color stability was determined by difference between coordinates obtained before and after the aging procedure. Data of color change and roughness were evaluated by ANOVA and Fisher's exact test (alpha = 0.05). Results: The results showed that the unsealed group had the highest color change compared to other groups (P = 0.0289), and there was no significant difference between groups sealed with surface sealant (P > 0.05). The artificial aging caused an increase in roughness values independent of the experimental group studied (P = 0.0015). Conclusion: The sealed composites showed lower color change after UV aging, but all groups showed clinically-acceptable color change, and only liquid polish decreased roughness.
Keywords: accelerated artificial aging; color stability; composite resin; roughness; surface sealant